MODERNIZATION OF FIQH IN CONTEMPORARY ERA: A Study of Yusuf Al-Qardhawi's Fiqh Thought - Hidayat, Muhammad; Rosele, Muhammad Ikhlas bin (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
This paper studies Islamic legal theory in Yusuf al-Qardhawi’s Fiqh thouagt. Although many  an academic have studied his thoughts in this field, Yusuf al-Qardhawi’s methodology in legal distillation or istinbat always considers social conditions and advances in science and technology. As such, the results of ijtihad (Fiqh) obtained are always in accordance with the times and space. Therefore, it is very natural if then the question arises whether Yusuf al-Qardhawi can be called a reformer of Fiqh in this modern era? Related to this issue, this paper seeks to reveal the facts that can be used as evidence that Yusuf al-Qardhawi can be called a Fiqh reformer or not, by exploring and analyzing all his thoughts on Islamic law in his works. Thus, in terms of its type, this paper is included in descriptive analytical library research. As a result of the discussion that has been done, it can be concluded that Yusuf al-Qardhawi can be called a reformer of Fiqh in this modern era, for taking milieu and the social dynamics into his account in legal finding. Keywords; Yusuf al-Qardhawi, reformer, fiqh, modern era.